Factors influencing community participation in protecting heritage sites in Lembah Bujang / Nur Syahirah Rusli and Tengku Fatin Auni Tengku Anuar - Rusli, Nur Syahirah; Tengku Anuar, Tengku Fatin Auni (2018)
The objective of this research is to study the relationship between motivation, opportunity and ability towards the community participation in protecting heritage site in Lembah Bujang. A total sample size of 106 respondents who are the community living in the three villages which are Kampung Pengkalan Bujang, Kampung Pengkalan Langgar and Kampung Sungai Gelam in Mukim Bujang. The respondents were selected to fill the set of questionnaire consist of 5 sections which are Demographic Information (Section A), Community Participation in protecting heritage site (Section B), Motivation (Section C), Opportunity (Section D) and Ability (Section D). The data was analyzed with Descriptive Statistic, Pearson Correlation and Multiple Regression using the Statistical Package for Social Sciences (SPSS) version 23. The result indicates that there were significant relationship motivation, opportunity, and ability towards the community participation in protecting heritage site. This study recommends that the community awareness group able to spread motivation and create awareness among the community in order to encourage the community to participate in protecting the heritage site.